2011
DOI: 10.1042/bj20101411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pendrin by pH: dependence on glycosylation

Abstract: Mutations in the anion exchanger pendrin are responsible for Pendred syndrome, an autosomal recessive disease characterized by deafness and goitre. Pendrin is highly expressed in kidney collecting ducts, where it acts as a chloride/bicarbonate exchanger and thereby contributes to the regulation of acid-base homoeostasis and blood pressure. The present study aimed to characterize the intrinsic properties of pendrin. Mouse pendrin was transfected in HEK (human embryonic kidney) 293 and OKP (opossum kidney proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…There are conflicting reports about whether or not these two sites are actually glycosylated in prestin (Matsuda et al, 2004;Navaratnam et al, 2005;Rajagopalan et al, 2010). Cell surface expression is unaffected by substitution of both asparagines with alanine residues, and these mutant proteins exhibited only minor alterations in their physiological properties (Matsuda et al, 2004;Navaratnam et al, 2005;Rajagopalan et al, 2010;Azroyan et al, 2011). However, recent evidence demonstrated that the mouse Slc26A4 paralog, pendrin, is glycosylated at the equivalent sites (N167 and N172) (Azroyan et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are conflicting reports about whether or not these two sites are actually glycosylated in prestin (Matsuda et al, 2004;Navaratnam et al, 2005;Rajagopalan et al, 2010). Cell surface expression is unaffected by substitution of both asparagines with alanine residues, and these mutant proteins exhibited only minor alterations in their physiological properties (Matsuda et al, 2004;Navaratnam et al, 2005;Rajagopalan et al, 2010;Azroyan et al, 2011). However, recent evidence demonstrated that the mouse Slc26A4 paralog, pendrin, is glycosylated at the equivalent sites (N167 and N172) (Azroyan et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Cell surface expression is unaffected by substitution of both asparagines with alanine residues, and these mutant proteins exhibited only minor alterations in their physiological properties (Matsuda et al, 2004;Navaratnam et al, 2005;Rajagopalan et al, 2010;Azroyan et al, 2011). However, recent evidence demonstrated that the mouse Slc26A4 paralog, pendrin, is glycosylated at the equivalent sites (N167 and N172) (Azroyan et al, 2011). Undoubtedly, these models are inadequate to explain the contribution of the MESH motif to the conformational changes of prestrin from the compact to expanded state, with membrane potential determining the probability of each conformation (Oliver et al, 2001;Dallos and Fakler, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Pendrin has been found to have a relatively high affinity to external chloride also at high pH value, which can be important to allow bicarbonate secretion in state of alkalosis [54]. Pendrin activity is also regulated by external pH.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of external pH is possibly related to allosteric modifications and represents an intrinsic pH effect. In vitro experiments in HEK cells demonstrated that sensitivity of pendrin to external pH depends on its glycosylation state [54]. Specifically, a low external pH stimulates pendrin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide also contributes to intercalated cell transport protein regulation as it reduces pendrin protein abundance in the kidney without modulating pendrin subcellular localization in a cAMP-dependent manner (103). The regulation of pendrin also involves glycosylation-dependent processes (104,105). In addition to the regulation of acid-base status, it appears that pendrin expressed in kidney intercalated cells plays a role in controlling iodide homeostasis as well, especially during high water intake (106).…”
Section: Type B Intercalated Cells and Their Transport Processesmentioning
confidence: 99%